Rhexodenticula aquatica (Sordariomycetidae genera incertae sedis), a novel hyphomycete from freshwater in Thailand - Dong, Wei; Zhang, Huang; Doilom, Mingkwan; Yu, Xian-Dong; Wang, Gen-Nuo; Nalumpang, Sarunya (Phytotaxa, 2021)
During our surveys of freshwater fungi on submerged wood in the Greater Mekong Subregion, a rhexodenticula-like taxon was collected, described and illustrated. The new collection is identified based on analyses of combined LSU, SSU, ITS and TEF sequence data, and morphological comparison with other Rhexodenticula species. According to the morphology and molecular analysis, our collection is not known before and hence, we introduce here as Rhexodenticula aquatica sp. nov. This species is characterized by macronematous, subcylindrical, unbranched conidiophores, polyblastic, terminal conidiogenous cells and fusiform, 3-septate, verruculose conidia, and schizolytic conidial secession. Rhexodenticula is referred to Sordariomycetidae genera incertae sedis due to its unstable phylogenetic placement in Sordariomycetidae.